STUDI PERTUMBUHAN ANAKAN POHON PADA PETAK PERMANEN DI HUTAN DATARAN RENDAH TAMAN NASIONAL GUNUNG GEDE PANGRANGO - Siti Sundari (Research Center for Biology-Indonesian Institute of Sciences, 2016)
Study of seedling growth was conducted at permanent plot in lowland forest of Gunung Gede Pangrango. The aim of this research was to determine the relationship between growth parameters such as number of seedling leaves, diameter, the depth of soil organic material and tree height of each seedling at the permanent subplot 5 x 5 m.The results showed that basal area, diameter, and the depth of soil organic material did not significantly affect on the number of seedling leaves, whereas basal area and the depth of soil organic material significantly affected on seedling diameter at each permanent subplot 5 x 5 m. For the trees height at the permanent subplot, it did not significantly affected on the number of seedling leaves, diameter, basal area and the depth of soil organic material. Diameter seedling and the depth of soil organic material were suspected as the main factors for the growth parameters of seedling growth in this area.